EFEKTIVITAS MESIN STAMPING DENGAN MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) DI PT. ALLIANCE CONSUMER PRODUCT INDONESIA (Jurnal Industri dan Teknologi Samawa, 2024)
Quality is a priority for almost all companies in the world. One factor in whether the quality of a product is good or not is the machines/equipment used effectively and efficiently. PT. Alliance Consumer Product Indonesia Medan is one of the industries engaged in manufacturing the Oleochemical (Bath Soap) Industry. The current problem is that Stamping machines are machines that often experience machine breakdowns compared to other production machines with a breakdown rate of 70 times/year with a time of 137.5 hours/year. This research aims to analyze various causes of the decline in the effectiveness of stamping machines using the concept of Overall Equipment Effectiveness (OEE), knowing the critical components of stamping machines with high Risk Priority Numbers that can be repaired to minimize failures that occur. The results showed that the overall equipment effectiveness (OEE) value ranged from 82.01% - 90.23%. The FMEA value obtained was that the component that had the main priority that had to be maintained was the molding with the largest risk value, namely 80, followed by the motor with a risk value of 45, blades. with a risk value of 24, sensors with a risk value of 16 and Endless Belt with a risk value of 12. Proposed improvements to labor factors and work methods